Accuracy of GFR Estimation in Obese Patients - Lemoine, Sandrine (American Society of Nephrology, 2014)
BACKGROUND AND OBJECTIVES: Adequate estimation of renal function in obese patients is essential for the classification of patients in CKD category as well as the dose adjustment of drugs. However, the body size descriptor for GFR indexation is still debatable, and formulas are not validated in patients with extreme variations of weight. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This study included 209 stages 1–5 CKD obese patients referred to the Department of Renal Function Study at the University Hospital in Lyon between 2010 and 2013 because of suspected renal dysfunction. GFR was estimated with the Chronic Kidney Disease and Epidemiology equation (CKD-EPI) and measured with a gold standard method (inulin or iohexol) not indexed (mGFR) or indexed to body surface area determined by the Dubois and Dubois formula with either real (mGFRr) or ideal (mGFRi) body weight. Mean bias (eGFR−mGFR), precision, and accuracy of mGFR were compared with the results obtained for nonobese participants (body mass index between 18.5 and 24.9) who had a GFR measurement during the same period of time. RESULTS: Mean mGFRr (51.6±24.2 ml/min per 1.73 m(2)) was significantly lower than mGFR, mGFRi, and eGFR(CKD-EPI). eGFR(CKD-EPI) had less bias with mGFR (0.29; −1.7 to 2.3) and mGFRi (−1.62; −3.1 to 0.45) compared with mGFRr (8.7; 7 to 10). This result was confirmed with better accuracy for the whole cohort (78% for mGFR, 84% for mGFRi, and 72% for mGFRr) and participants with CKD stages 3–5. Moreover, the Bland Altman plot showed better agreement between mGFR and eGFR(CKD-EPI). The bias between eGFR(CKD-EPI) and mGFRr was greater in obese than nonobese participants (8.7 versus 0.58, P<0.001). CONCLUSIONS: This study shows that, in obese CKD patients, the performance of eGFR(CKD-EPI) is good for GFR≤60 ml/min per 1.73 m(2). Indexation of mGFR with body surface area using ideal body weight gives less bias than mGFR scaled with body surface area using real body weight.